Fatty acid profile of Greek yogurt with colostrum addition - GOMES, Rhaabe Dayane da Silva; BARBOSA, Idiana de Macedo; RIBEIRO, Cláudio Vaz Di Mambro; ANAYA, Katya; SILVA, Emerson Gabriel dos Santos Oliveira; OLIVEIRA, Chiara Albano de Araujo; GAMA, Marco Antonio Sundfeld da; OLIVEIRA, Juliana Paula Felipe de; SALE, Danielle Cavalcanti; ARAÚJO, Emmanuella de Oliveira Moura; RANGEL, Adriano Henrique do Nascimento (Food Science and Technology, 2023)
The nutraceutical properties of colostrum have stimulated interest in its use in the production of functional foods and supplements that benefit human health. This study investigated the fatty acid profile of Greek yogurt formulations added with bovine colostrum. Four formulations of Greek yogurt were developed with different colostrum levels: 0, 10, 20, and 30%. Next, fat extraction and esterification were performed to determine the fatty acid profile. Then, the concentrations of fatty acid methyl esters were determined by gas chromatography. No effect was observed for the C14:0, C16:0, and C18:0 concentrations with the addition of colostrum. Although the C18:1c9, C18:2n6, C18:3n3, and C20:4n6 concentrations were not affected by colostrum, the C16:1c9, polyunsaturated fatty acids, and n-6 fatty acid contents increased, without changes in the n-6 to n-3 ratio. C18:1t9 was the only monounsaturated fatty acid that differed among formulations and it increased with colostrum addition. There was no effect of the colostrum increase on the total saturated, unsaturated, and monounsaturated fatty acid concentrations. The bovine colostrum used as an ingredient in Greek yogurt showed slight changes in the fatty acid profile. The use of colostrum is an alternative to reduce costs and maintain health benefits.